2018
DOI: 10.4196/kjpp.2018.22.2.183
|View full text |Cite
|
Sign up to set email alerts
|

Berberine alleviates symptoms of anxiety by enhancing dopamine expression in rats with post-traumatic stress disorder

Abstract: Post-traumatic stress disorder (PTSD) is a trauma-induced psychiatric disorder characterized by impaired fear extermination, hyperarousal, anxiety, depression, and amnesic symptoms that may involve the release of monoamines in the fear circuit. The present study measured several anxiety-related behavioral responses to examine the effects of berberine (BER) on symptoms of anxiety in rats after single prolonged stress (SPS) exposure, and to determine if BER reversed the dopamine (DA) dysfunction. Rats received B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…Some studies suggested that Elettaria cardamomum methanolic extract significantly recovered anxiety-like behaviors in a rat model of PTSD conducted by the OFT, EPM, and rotarod tests [ 38 ]. Also, administering berberine, an isoquinoline alkaloid derived from Korean traditional medicinal herbs, such as Coptidis Rhizoma after SPS procedure, significantly increased the time spent in the open arms in the EPM and prevented reduction in brain level of dopamine [ 39 ]. Therefore, herb-derived compounds could lead to the development of novel therapeutics for treating PTSD.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies suggested that Elettaria cardamomum methanolic extract significantly recovered anxiety-like behaviors in a rat model of PTSD conducted by the OFT, EPM, and rotarod tests [ 38 ]. Also, administering berberine, an isoquinoline alkaloid derived from Korean traditional medicinal herbs, such as Coptidis Rhizoma after SPS procedure, significantly increased the time spent in the open arms in the EPM and prevented reduction in brain level of dopamine [ 39 ]. Therefore, herb-derived compounds could lead to the development of novel therapeutics for treating PTSD.…”
Section: Discussionmentioning
confidence: 99%
“…Depression is the most common mental disorder in humans. Berberine upregulated BDNF expression in the hippocampus to lessen corticosterone‐induced depressive‐like behavior in mice 322 and enhanced dopamine expression to alleviate symptoms of anxiety in rats with posttraumatic stress disorder 323 . It also exerted antidepressant‐like effects in ovariectomized mice and decreased immobility time in a dose‐dependent manner.…”
Section: Bioactivitiesmentioning
confidence: 99%
“…Lycorine-type alkaloids, including lycorine(321), acetycaranine(322), caranine(323), galanthine(324), 9-Odemethylgalanthine (325), as well as α-crinane types, haemanthamine (326), haemanthidine (327), and β-crinane types, ambelline (328), 11-O-acetylambelline (329), 1-O-acetylbulbisine (330), undulatine (331), crinamidine (332), buphanamine (333), and srinine (334), were isolated from Zephyranthes robusta, Chlidanthus fragrans, Nerine bowdenii, and Narcissus poeticus cv. Brackenhurst by Cahlíková and collegaues, these compounds show moderate F I G U R E 15 The chemical structures of compounds 299−320 SHANG ET AL.…”
mentioning
confidence: 99%
“…Berberine, an OTC medication in China, has been verified well for safety in clinical trials (Gupte, 1975). Besides, previous studies have shown that berberine affected the DA and N-methyl-D-aspartate (NMDA) systems, which is the molecular mechanism of cognitive enhancers (Yoo et al, 2006;Kaplan and Moore, 2011;Kawano et al, 2015;Lee et al, 2018). Shen et al (2020) demonstrated that extinction training combined with berberine treatment facilitated the extinction of drug memory.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, berberine modulates oxytocin receptors to attenuate methamphetamine consumption and anxiety-like behaviors (Alavijeh et al, 2019). Furthermore, berberine has been reported to alleviate anxiety-like behavior in rats with posttraumatic stress disorder and facilitate extinction of drug memories (Lee et al, 2018;Shen et al, 2020). In Shen and colleagues' study, they found that brain-derived neurotropic factor (BDNF) and AMPA receptors (GluA1 and GluA2) were associated with enhanced extinction memory consolidation (Shen et al, 2020).…”
Section: Introductionmentioning
confidence: 99%